Scoping Review: Analysis of Occupational Stress Levels and Their Associated Factors Among Firefighters - Puteri, Febyona Jolest; Erwandi, Dadan (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Firefighting is a high-stress occupation due to exposure to situations involving extinguishing fires, saving lives, and protecting the property of people affected by fire incidents. The aim of this study was to identify stress-related factors and association in firefighters. A systematic review following the PRISMA 2020 V1 statement was carried out in the Science Direct and Google Scholar databases. The literature search was conducted in April 2025. A total of 12 studies were included in this review. Based on the result and discussion, burnout in firefighters happens because of a mix of different factors such as mental pressure, personal background, behavior, and workplace conditions. When firefighters face heavy workloads, frequent emergencies, poor sleep, and lack healthy ways to handle stress, it can lead to serious mental health problems. A bad work environment only makes things worse. These issues not only affect their personal well-being but also reduce their job performance and put safety at risk. Therefore, it is recommended that fire departments and related institutions implement comprehensive strategies to address these risks. In addition, interventions such as stress management training, regular health screenings, and improvements in the work environment should be prioritized to reduce burnout and enhance the quality of life and performance among firefighters.